Question
upstudy study bank question image url

3) Consider the quadratic \( f(x)=-2 x^{2}-4 x+5 \). \( \begin{array}{ll}\text { a. What is the average rate of change over } & \text { b. What is the average rate of change over } \\ \text { the interval from } x=0 \text { to } x=2 \text { ? } & \text { the interval from }-7 \leq x \leq-4 ?\end{array} \)

Ask by Lane Pope. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The average rate of change from \( x = 0 \) to \( x = 2 \) is **-8**, and from \( x = -7 \) to \( x = -4 \) is **18**.

Solution

To determine the average rate of change of the quadratic function \( f(x) = -2x^2 - 4x + 5 \) over specified intervals, we'll use the formula: \[ \text{Average Rate of Change} = \frac{f(b) - f(a)}{b - a} \] where \( a \) and \( b \) are the endpoints of the interval. --- ### **a. Average Rate of Change from \( x = 0 \) to \( x = 2 \)** 1. **Calculate \( f(0) \):** \[ f(0) = -2(0)^2 - 4(0) + 5 = 0 - 0 + 5 = 5 \] 2. **Calculate \( f(2) \):** \[ f(2) = -2(2)^2 - 4(2) + 5 = -2(4) - 8 + 5 = -8 - 8 + 5 = -11 \] 3. **Compute the Average Rate of Change:** \[ \frac{f(2) - f(0)}{2 - 0} = \frac{-11 - 5}{2} = \frac{-16}{2} = -8 \] **Answer:** The average rate of change from \( x = 0 \) to \( x = 2 \) is **-8**. --- ### **b. Average Rate of Change from \( x = -7 \) to \( x = -4 \)** 1. **Calculate \( f(-7) \):** \[ f(-7) = -2(-7)^2 - 4(-7) + 5 = -2(49) + 28 + 5 = -98 + 28 + 5 = -65 \] 2. **Calculate \( f(-4) \):** \[ f(-4) = -2(-4)^2 - 4(-4) + 5 = -2(16) + 16 + 5 = -32 + 16 + 5 = -11 \] 3. **Compute the Average Rate of Change:** \[ \frac{f(-4) - f(-7)}{-4 - (-7)} = \frac{-11 - (-65)}{3} = \frac{54}{3} = 18 \] **Answer:** The average rate of change from \( x = -7 \) to \( x = -4 \) is **18**. --- **Summary:** - **a.** Average rate of change from \( x = 0 \) to \( x = 2 \) is **-8**. - **b.** Average rate of change from \( x = -7 \) to \( x = -4 \) is **18**.

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Extra Insights

To find the average rate of change of the function \( f(x) = -2x^2 - 4x + 5 \) over an interval, we use the formula: \[ \text{Average Rate of Change} = \frac{f(b) - f(a)}{b - a} \] **For part a**, over the interval from \( x = 0 \) to \( x = 2 \): First, calculate \( f(0) \) and \( f(2) \): \[ f(0) = -2(0)^2 - 4(0) + 5 = 5 \] \[ f(2) = -2(2)^2 - 4(2) + 5 = -8 - 8 + 5 = -11 \] Then plug these values into the average rate of change formula: \[ \text{Average Rate of Change} = \frac{f(2) - f(0)}{2 - 0} = \frac{-11 - 5}{2 - 0} = \frac{-16}{2} = -8 \] The average rate of change over the interval from \( x = 0 \) to \( x = 2 \) is \(-8\). **For part b**, over the interval from \( -7 \) to \( -4 \): Calculate \( f(-7) \) and \( f(-4) \): \[ f(-7) = -2(-7)^2 - 4(-7) + 5 = -2(49) + 28 + 5 = -98 + 28 + 5 = -65 \] \[ f(-4) = -2(-4)^2 - 4(-4) + 5 = -2(16) + 16 + 5 = -32 + 16 + 5 = -11 \] Now, apply the average rate of change formula: \[ \text{Average Rate of Change} = \frac{f(-4) - f(-7)}{-4 - (-7)} = \frac{-11 - (-65)}{-4 + 7} = \frac{-11 + 65}{3} = \frac{54}{3} = 18 \] The average rate of change over the interval from \( -7 \) to \( -4 \) is \( 18 \).

Related Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy